Stress Role and Dysfunctional Behavior on The Performance of Internal Auditor - Rieke Sri Rizki (Faculty of Economics and Business, University of Pasundan, 2015)
This study intends to show the relationship of stress role including role conflict and role ambiguity with dysfunctional behavior, and its effect on the performance of internal auditors at BO of BJB Bank. The research design is explanatory survey, with a population of internal auditors (internal controls) throughout BO of BJB Bank which is also a sample. The type of data is cross-section with a collection of questionnaires. The method used is path analysis. The analysis showed: 1) role conflict and role ambiguity did not have a positive effect on the dysfunctional behavior of internal auditor; 2) role conflict and role ambiguity did not adversely affect the performance of the internal auditor; and 5) dysfunctional behavior did not negatively affects the performance of the internal auditor. The reason is that the internal auditors have adequate skills and knowledge in every BO of BJB Bank, so they can control the condition of stress role experienced in low levels. Stressful conditions can serve as constructive stress that brings a positive impact that suppress the emergence of dysfunctional behavior and make stress as a spur to improve their performance.